MEXICAN BIBLIOGRAPHY ON NATURAL HISTORY - MALDONADO KOERDELL, MANUEL (Loyola Universidad Sch Med, Chicago, EUA, 1947)
P tadaridae (Nematoda: Trichostrongylidae), an intestinal parasite of the bats, is described
REV SOC MEX HIST NAT
Keywords: MEXICAN BIBLIOGRAPHY, NATURAL HISTORY; CIENCIAS DE LA VIDA